Long Noncoding RNAs: A New Regulatory Code in Metabolic Control. Issue 10 (October 2015) - Zhao, Xu-Yun; Lin, Jiandie D.
<x xml:space="preserve">Abstract</x> Long noncoding RNAs (lncRNAs) are emerging as an integral part of the regulatory information encoded in the genome. lncRNAs possess the unique capability to interact with nucleic acids and proteins, and exert discrete effects on numerous biological processes. Recent studies have delineated multiple lncRNA pathways that control metabolic tissue development and function. The expansion of the regulatory code that links nutrient and hormonal signals to tissue metabolism gives new insights into the genetic and pathogenic mechanisms underlying metabolic disease. This review discusses lncRNA biology with a focus on their role in the development, signaling, and function of key metabolic tissues.